2012
DOI: 10.1044/1092-4388(2011/11-0065)
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in the Processing of Vowel Height

Abstract: We take our results to reflect an abstract long-term representation of vowels that do not include redundant specifications at very early stages of processing the speech signal. Moreover, the dipole locations indicate extraction of distinctive features and their mapping onto representationally faithful cortical locations (i.e., a feature map).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 79 publications
6
52
0
Order By: Relevance
“…For example, Scharinger, Monahan, and Idsardi (2012) examined the underspecification of vowel height in three English vowels. Consistent with the previous German studies, a larger MMN response was observed when the underspecified vowel /ε/, as in “bet” was the deviant, as compared to a vowel with a more specified height, /æ/, as in “bat” (Scharinger, Monahan, & Idsardi, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Scharinger, Monahan, and Idsardi (2012) examined the underspecification of vowel height in three English vowels. Consistent with the previous German studies, a larger MMN response was observed when the underspecified vowel /ε/, as in “bet” was the deviant, as compared to a vowel with a more specified height, /æ/, as in “bat” (Scharinger, Monahan, & Idsardi, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Scharinger, Monahan, and Idsardi (2012) examined the underspecification of vowel height in three English vowels. Consistent with the previous German studies, a larger MMN response was observed when the underspecified vowel /ε/, as in “bet” was the deviant, as compared to a vowel with a more specified height, /æ/, as in “bat” (Scharinger, Monahan, & Idsardi, 2012). In contrast, Scharinger et al (2011) examined [coronal] underspecification in two English consonant manner classes: glides (/w/ and /j/) and fricatives (/v/ and /ʒ/), with /w/ and /v/ classified as [labial] and /j/ and /ʒ/ classified as [coronal].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been proposed that less specific, underspecified vowels have less intrinsic “predictive” value compared to more specific, specified vowels (Eulitz and Lahiri, 2004; Scharinger et al, 2012a; Scharinger et al, 2012b). Scharinger et al (2012b) demonstrated that the unspecific category structure of the American English vowel [ε] influenced processing, as indexed by the Mismatch Negativity, an automatic change and prediction error response of the brain (Näätänen and Alho, 1997; Schröger, 2005; Winkler, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Scharinger et al (2012b) demonstrated that the unspecific category structure of the American English vowel [ε] influenced processing, as indexed by the Mismatch Negativity, an automatic change and prediction error response of the brain (Näätänen and Alho, 1997; Schröger, 2005; Winkler, 2007). In a passive oddball design, the authors contrasted the high- and low-vowels [ɪ] and [æ] in standard position with the low- and high-vowels [æ] and [ɪ] in deviant position.…”
Section: Introductionmentioning
confidence: 99%
“…At the most abstract end of the spectrum, lexical underspecification models (e.g., Lahiri & MarslenWilson, 1991) posit that listeners store abstract lexical representations whose content is underspecified for predictable or default information (e.g., Archangeli, 1988;Archangeli & Pulleyblank, 1989;Dinnsen, 1996;Pulleyblank, 1986Pulleyblank, , 1988aPulleyblank, , 1988bRingen, 1988;Stemberger, 1991;Stemberger & Stoel-Gammon, 1991). During word recognition, listeners determine whether features extracted from a surface form match the stored features; when features are underspecified, they neither support activation of the target word nor elicit a mismatch (Eulitz & Lahiri, 2004;Lahiri & Marslen-Wilson, 1991;Pallier et al, 2001;Scharinger et al, 2012;Wheeldon & Waksler, 2004). As a result, a listener can accept surface greem as a possible match for underlying green, because the coronal sound in /ɡrin/ is underspecified for place and does not therefore mismatch with the [labial] feature of the surface form.…”
Section: Introductionmentioning
confidence: 99%